Studi Kelayakan Bisnis Analisis Aspek Lingkungan Koperasi Omah Susu - jasmine, ken catri amira (Maliki Interdisciplinary Journal, 2025)
This report presents a feasibility study of the "Omah Susu" Milk Cooperative business which aims to improve the welfare of local dairy farmers and provide high quality dairy products for the community. Founded in 2021, this cooperative integrates the principles of cooperation, desire and innovation in its management. By producing various fresh milk products, such as whole milk, yogurt and cheese, "Omah Susu" is committed to meeting health and quality standards through modern technology and training for farmers. This report outlines an analysis of legal, environmental, market and technical aspects that influence cooperative operations. Despite meeting many legal requirements, challenges such as NIB control and market competition remain. The cooperative is also active in educating the public about the importance of milk consumption and healthy lifestyles. Through effective marketing strategies, "Omah Susu" strives to build an independent community and improve the quality of life of its members and the surrounding community. It is hoped that this report can become a reference for business development and cooperative aspirations in the future.